Studi Penempatan Sumur Resapan Berdasarkan Nilai Laju Infiltrasi, Kualitas Fisik Air, dan Tekstur Tanah pada DAS Air Dingin dan Batang Kandis Bagian Tengah-Hilir, Kota Padang - Rizka Mutiara; Rusli HAR (Journals Mining Engineering : Bina Tambang, 2019)
Abstract. Spontaneous resettlement of people to the eastern part of Padang City which is a catchment area and the development continues so that open land shifts function to residential land, offices, etc. This causes a reduction in catchment areas which can result in flooding and decreasing environmental quality, especially groundwater. To minimize the occurrence of flooding in the Air Dingin and Batang Kandis Watershed a placement study of infiltration wells based on the infiltration rate, physical quality of water, and soil texture. This research was conducted in 41 points in the middle to downstream of the Air Dingin and Batang Kandis Watershed. Data obtained in the form of physical quality data of water, soil texture, and other supporting data. Based on infiltration rate data, the average infiltration rate in the study area of 0.11826 cm / minute is classified of low recharge areas (<0.5 cm / minute). After doing the research by looking at statistical analysis, physical quality of water, soil texture, lithological of rocks, and land use in the Air Dingin and Batang Kandis watersheds. Then the placement of infiltration wells is spread over 20 points in the Air Dingin and Batang Kandis Watershed in Padang City.  Keywords: Infiltration Wells, Infiltration Rate, Physical Quality of Groundwater, Soil Texture, Rock Lithology